2012
DOI: 10.1121/1.4709008
|View full text |Cite
|
Sign up to set email alerts
|

Syllables intelligibility in relation to the autocorrelation and cepstrum model: the case of Chinese in Taiwan

Abstract: The articulation of some special pronunciations of vowel inconsistently raises with the rapid speech transmission index (RASTI) tested using monosyllables for Chinese phonics. In the researching of speech intelligibility in room, the factors being considered have to include not only the qualities of sound field but the pronunciation characteristics of syllables as well. Therefore, with regard to the defect of RASTI measurements, we utilized the autocorrelation and the cepstrum of monosyllables recorded in room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The speech intelligibility for the monosyllables of Chinese in Taiwan area are in agreement with the effective duration of autocorrelation function (τe) of the syllable itself in the same reverberation levels were found (Chen and Chan [21]). On the contrary, it was found (Chen [22]) that they are opposite between speech transmission index (STI proposed by Steeneken and Houtgast [23]) and magnitude of inter-aural cross-correlation (IACC) where the slope of ceiling were changed in the hall.…”
Section: An Approach On Speech Intelligibility Regarding Binaural Sensupporting
confidence: 82%
See 1 more Smart Citation
“…The speech intelligibility for the monosyllables of Chinese in Taiwan area are in agreement with the effective duration of autocorrelation function (τe) of the syllable itself in the same reverberation levels were found (Chen and Chan [21]). On the contrary, it was found (Chen [22]) that they are opposite between speech transmission index (STI proposed by Steeneken and Houtgast [23]) and magnitude of inter-aural cross-correlation (IACC) where the slope of ceiling were changed in the hall.…”
Section: An Approach On Speech Intelligibility Regarding Binaural Sensupporting
confidence: 82%
“…Similarly, Licklider [34] investigated IACC's effect on word-intelligibility under noise masking and found that except the effect of SN ratio, decrease of IACC could improve word-intelligibility in the way that mono-syllables were replaced by short sentences. Chen [35] arranged the recordings of monosyllables in 7 halls, and found that effect both word-difficulty and word-intelligibility could be separated clearly using accumulated cepstrum of the speech voice.…”
Section: Subjective Word Intelligibility In Sound Fieldmentioning
confidence: 99%
“…In the earlier study by Chen and Ando [15], 100 Hz α-waves and 500 Hz β-waves were sampled according to the sampling frequency laws and, after A/D conversion (16 bits), input into a computer to calculate the effective duration (τ e ) of CBWs' ACF ( Figure 4). In ACF calculations of τ e values in the study by Chen and Chan [16], the 0.3 s integration time (2 T) of monosyllabic speech sounds was suggested to be the most effective. Eventually, the monosyllabic signals were played in this study included simulation of the first delay time [17].…”
Section: Brainwave Analysis Methodsmentioning
confidence: 99%
“…The electrode system was grounded each time the brainwaves were recorded in order to avoid external electric interference. The settings of the simulated sound field were similar to that in the aforementioned psychological experiment [16]. The collected brainwave data was analyzed and processed by NI LabVIEW software.…”
Section: Brainwave Recording Methodsmentioning
confidence: 99%
“…12 subjects, all of whom self-reported as being right-handed and having normal hearing, participated in this experiment. The number of participants demanded for the CBW recordings was referred to as the conventional studies [1][2][3][4][5][6], which met the requirements for analysing the sound field characteristics.…”
Section: Recording Of Continuous Brainwaves (Cbw)mentioning
confidence: 99%